The liberty to take fish : Atlantic fisheries and federal power in nineteenth-century America - Earle, Thomas Blake (Cornell University Press, 2023)
"This book examines the central role commercial fishing in the North Atlantic played in the development of American statecraft from the American Revolution through the Civil War Era"--